Lead Poisoning: differential diagnosis of chronic abdominal pain. Case report and review - Moreno, Atilio; Hospital Universitario San Ignacio (Pontificia Universidad Javeriana, 2012)
This article presents a case of chronic lead poisoning, which principal manifestation was abdominal pain. This usually occurs in patient who works with the metal. We reviewed the most frequent clinical manifestation and management. If is untreated this poisoning has a high morbidity and mortality.